2013
DOI: 10.1002/pros.22704
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signatures of aggressive prostate cancer

Abstract: BACKGROUND. Current diagnostic techniques have increased the detection of prostate cancer; however, these tools inadequately stratify patients to minimize mortality. Recent studies have identified a biochemical signature of prostate cancer metastasis, including increased sarcosine abundance. This study examined the association of tissue metabolites with other clinically significant findings. METHODS. A state of the art metabolomics platform analyzed prostatectomy tissues (331 prostate tumor, 178 cancer-free pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 54 publications
(67 reference statements)
12
115
1
Order By: Relevance
“…Studies profiled metabolomic features of prostatectomy tissues from two independent cohorts of PCa patients (331 prostate tumour-containing samples and 178 tumour-free prostate samples) [12]. They found that prostate tumours had significantly altered metabolite profiles compared to cancer-free prostate tissues, including biochemicals associated with cell growth, energetics, stress, and loss of prostate-specific biochemistry.…”
Section: Prostarix (Metabolon)mentioning
confidence: 99%
“…Studies profiled metabolomic features of prostatectomy tissues from two independent cohorts of PCa patients (331 prostate tumour-containing samples and 178 tumour-free prostate samples) [12]. They found that prostate tumours had significantly altered metabolite profiles compared to cancer-free prostate tissues, including biochemicals associated with cell growth, energetics, stress, and loss of prostate-specific biochemistry.…”
Section: Prostarix (Metabolon)mentioning
confidence: 99%
“…The Gleason biopsy grade is used in conjunction with other clinical and molecular variables, including serum PSA levels and clinical stage, to help make treatment decisions for prostate cancer and they are all incorporated into various ''nomograms'' to Responsible Editor: John Di Battista. determine pre-operatively the risk of progression after specific therapy [11,12]. Although several tools with potential clinical value have been proposed [13][14][15], there is still no reliable index for predicting the outcome of prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[65][66][67][68][69][70][71][72] Future advances in the area of prognostic genomics could include the development of a gene signature that could enable clinicians to assign patients to treatment escalation (for example increasing the dose of IGRT that patients receive or a adding systemic therapy such as ADT) or de-escalation (with no requirement for systemic therapy) protocols on the basis of diagnostic biopsy, thus providing a priori information regarding a patient's likelihood of experiencing treatment failure. 73 The use of these invasive and/or noninvasive assays might help to better define the fraction of patients harbouring occult metastases whom could benefit from combined ADT-IGRT and improve their survival o utcomes (Box 2).…”
Section: Occult Metastases and Adt-igrtmentioning
confidence: 99%